Pedagogical content knowledge for teaching numbers and operations: a study with prospective teachers - André Joaquim; Paula Catarino; Maria Nascimento; Ana Paula Aires (Millenium)
Introduction: The mission of Initial Teacher Education (ITE) is to prepare future teachers for teaching with the basic scientific, technical, and pedagogical skills and knowledge for the professional performance of teaching practice, in particular content and pedagogical content knowledge (PCK).